The Fleshy Fungi, Sparassis crispa (Basidiomycetes: Polyporales) from Nepal - Devkota, Shiva (Scientific World, 2010)
A cauliflower mushroom, collected at the bases of oak and conifers in different localities of Langtang National Park, Central Nepal is identified as Sparassis crispa (Wulf.) Fr. The taxonomic approach has been made here along with distribution notes. Key words: Sparassis; Taxonomy; Langtang; Distribution; Edible mushrooms. DOI: 10.3126/sw.v7i7.3835 Scientific World Vol.7(7) 2009 pp.94-95